Paraphilia without symptoms of primary psychiatric disorder: a case report - Pang, Nicholas Tze Ping; Masiran, Ruziana; Alimuddin, Aishah Siddiqah (BioMed Central, 2023)
Background: Paraphilias are recurrent and arousing fantasies, thoughts, and behaviors that cause distress to suferers and surrounding people. This case report details the challenge of managing multiple paraphilias with compulsive sexual behavior. Case presentation: A 48-year-old Malay man presented with compulsive sexual behavior, encompassing voyeuristic, frotteurism, and exhibitionistic behavior, increasing progressively over the years, with accompanying overvalued ideas of erotomania. Despite the high level of dysfunction occupationally and socially, there were no apparent psychotic, manic, or depressive symptoms. An organic workup was unremarkable, and he was diagnosed with multiple paraphilias. Treatment with selective serotonin reuptake inhibitors was commenced, and psychologically he was managed with techniques specifc to compulsive sexual behavior. Conclusion: Though rare in the literature, both paraphilic disorders and compulsive sexual behaviors are very distressing to suferers and their families alike, and thorough biopsychological investigations are essential to ensure reversible causes are not overlooked.